Peningkatan Kompetensi guru Akuntansi dalam Pengajaran Komputer Akuntansi - Santi, Elfitri; Mustika, Rasyidah; Endrawati (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
The development of technology has been very rapid and the curriculum has lagged far behind. This requires a curriculum change. SMK has made this change but in its development it is no longer relevant. Teachers as the spearhead of successful learning in schools must have competencies that are relevant to the development needs of the industry. This activity aims to improve the ability of Accounting MGMP teachers in West Sumatra province in learning computer accounting (Accurate). The approach taken in this research is a case study. The training process starts from application installation, creation of new company files, input transactions, and preparation of financial reports. The activity went well, but some teachers still needed further training and a whatsapp group was formed for further discussion. The obstacles faced were participants who were not familiar with computers.